Efficacy of YL-1 hematoma crushing needle combined with hematoma drainage in intracerebral hemorrhage treatment - Chen, Xianyong; Chen, Danhong; Sun, Shaonan; Huang, Zhenyong; Hu, Weipeng; Zhu, Qiangbin (Frontiers in Medicine, 2025)
ObjectiveEarly craniotomy evacuation in hematoma surgery does not significantly improve the prognosis of patients with spontaneous intracerebral hemorrhage (ICH). The YL-1 hematoma crushing puncture needle, specifically designed for ICH evacuation, has an uncertain therapeutic efficacy. This study aimed to evaluate its clinical effectiveness.Materials and methodsWe retrospectively reviewed medical records of patients with ICH who underwent twist intraosseous drill needle (TIDN) surgery at our institution between September 2016 and March 2023. Clinical outcomes were analyzed.ResultsThe surgical group demonstrated a significantly shorter hematoma resolution time, averaging 14.71 days less than the conservative group (p < 0.001). The Barthel Index improved more in the surgical group, with an average increase of 8.214 points (p < 0.001). Seven days post-admission, the increase in Glasgow Coma Scale (GCS) scores was significantly higher in the surgical group, with an average improvement of 1.471 points (p < 0.001). Additionally, the duration of mannitol administration was significantly reduced in the surgical group (p < 0.001).ConclusionTIDN surgery combined with hematoma drainage may serve as a viable surgical alternative for basal ganglia hemorrhage patients. This approach appears to reduce mannitol usage, mitigate craniotomy-associated risks, and promote short-term improvements in GCS scores and Barthel Index, highlighting its potential clinical benefits.